Flow patterns and water wetting in oil-water two phase flow - A flow loop study - Kee, K.E. (National Assoc. of Corrosion Engineers International, 2014)
Carbon steel pipelines used for transporting oils generally have some water flowing concurrently with the oil phase. The presence of water can lead to internal corrosion problems when free water contacts/wets the pipe wall surface. Therefore, it is pertinent to study how the distribution of water under different oil-water flow conditions can affect the steel surface wetting, i.e. whether the wall surface is wetted by water or oil phase. In this experimental work, a large scale 0.1m ID inclinable flow loop was used to study the two phase oil-water flow in horizontal and vertical positions. Paraffinic model oil and 1wt NaCl aqueous solutions were utilized as the test fluids. Two measurement techniques: flush mounted conductivity pins and high speed camera were employed for surface wetting determination and flow patterns visualization, respectively. The wetting data were classified based on four types of wetting behaviors: stable water wet, unstable water wet, unstable oil wet, and stable oil wet. The wetting results from the conductivity pins were found to match with the visualization results from the high speed camera. The horizontal oilwater flow results showed that water flows separately and wets the pipe bottom at low mixture liquid velocity. Moreover, not all of the water is fully dispersed at higher mixture liquid velocities, as traces of water can still be found to wet the surface intermittently. Â© 2014 by NACE International.